Extended prioritizing of store plan alternatives produced with shape grammar using the generalized Choquet integral method - Özdemir, Yavuz; Özdemir, Şahika; Özdemir, Şahika (Sage Publications Ltd., 2019)
In the previous paper, the store plan alternatives produced with shape grammar were evaluated using two of multi-criteria decision making techniques with triangular fuzzy numbers, namely fuzzy Analytic Hierarchy Process and fuzzy ANP. In addition to fuzzy Analytic Hierarchy Process and fuzzy ANP results, another multi-criteria decision making technique, the generalized Choquet integral method with trapezoidal fuzzy numbers, is used for evaluation and the result of this method is compared with fuzzy Analytic Hierarchy Process and fuzzy ANP results. The main contribution of this paper is to determine the interdependency among main criteria and subcriteria, the nonlinear relationship among them and the environmental uncertainties while prioritizing plan alternatives using the generalized Choquet integral method with the experts' same data that evaluated in the previous study. To the authors' knowledge, this will be the first interdisciplinary study which uses the generalized Choquet integral method in the field of architectural design.
WOS: 000471881100009
Keywords: Computer-aided design; Choquet integral; shape grammars; store design; decision making